Patent Ductus Arteriosus in Preterm Infants: Do We Have the Right Answers?. (23rd December 2013) - Abdel-Hady, Hesham; Nasef, Nehad; Shabaan, Abd Elazeez; Nour, Islam
Abstract : Patent ductus arteriosus (PDA) is a common clinical condition in preterm infants. Preterm newborns with PDA are at greater risk for several morbidities, including higher rates of bronchopulmonary dysplasia (BPD), decreased perfusion of vital organs, and mortality. Therefore, cyclooxygenase (COX) inhibitors and surgical interventions for ligation of PDA are widely used. However, these interventions were reported to be associated with side effects. In the absence of clear restricted rules for application of these interventions, different strategies are adopted by neonatologists. Three different approaches have been investigated including prophylactic treatment shortly after birth irrespective of the state of PDA, presymptomatic treatment using echocardiography at variable postnatal ages to select infants for treatment prior to the duct becoming clinically significant, and symptomatic treatment once PDA becomes clinically apparent or hemodynamically significant. Future appropriately designed randomized controlled trials (RCTs) to refine selection of patients for medical and surgical treatments should be conducted. Waiting for new evidence, it seems wise to employ available clinical and echocardiographic parameters of a hemodynamically significant (HS) PDA to select patients who are candidates for medical treatment. Surgical ligation of PDA could be used as a back-up tool for those patients who failed medical treatment and continued to have hemodynamic compromise.